Force Control for One Degree of Freedom Haptic Device using PID Controller - Abdul Rahman, Hisyam; Mohamad Husni, Nur Amirah; A. JALIL @ ZAINUDDIN, Mohd Hafiz; HANAFI, DIRMAN; Ksm Kader Ibrahim, Babul Salam; Muhamad Saiful Huq; Ahmmad, Siti Nor Zawani (International Journal of Integrated Engineering, 2020)
Haptics has been used as an additional feedback to increase human experience to the environment over years and its application has been widening into education, manufacturing and medical. The most developed haptic devices are for rehabilitation purpose. The rehabilitation process usually depends on the physiotherapist. But, it requires repetitive movements for long-term rehabilitation, thus haptic devices are needed. Most of the rehabilitation devices are included with haptic feedback to enhance therapy exercise during the rehabilitation process. However, the devices come with multiple degrees of freedom (DOF), complex design and costly. Rehabilitation for hand movement such as grasping, squeezing, holding and pinching usually does not need an expensive and complex device. Therefore, the goal of this study is to make an enhancement to One DOF Haptic Device for grasping rehabilitation exercise. It is improved to perform a force control mechanism with few types of conventional controller which are Proportional (P) controller, Proportional-Integral (PI) controller, Proportional-Derivative (PD) controller and Proportional-Integral-Derivative (PID) controller. The performance of the haptic device is tested with different conventional controller to obtain the best proposed controller based on the lowest value of Mean Square Error (MSE). The results show that PID Controller (MSE = 0.0028) is the most suitable for the haptic device with Proportional gain (Kp), Integral gain (Ki) and Derivative gain (Kd) are 1.3, 0.01 and 0.2 respectively. The force control mechanism can imitate the training motion of grasping movement for the patient.